Avaliação em larga escala e qualidade da educação: um estudo a partir da visão dos sujeitos da Rede Escolar Municipal de Cachoeirinha/RS - Tavares, Edson Leandro Hunoff (Universidade do Vale do Rio dos Sinos, 2013)
In this research, we contextualize educational policies related to large-scale evaluation of the quality of basic education in Brazil, demonstrating concrete reflections of the capitalist mode of production, and neoliberal globalization in our education. We investigate, from the perspective of the subjects in the municipal school Cachoeirinha / RS, the contradictions existing educational policies related to process large-scale evaluation of the quality of education of the city and its schools of primary education, especially in final series of: EMEF Portugal, E.M.E.F. Antônio Carlos Wilkens and E.M.E.F. Getúlio Vargas. We conducted a qualitative study of natures dialectical and historical-criticism, expressed in historical materialism. We conducted a case study in which we investigate empirically the vision and categorize subjects' municipal school Cachoeirinha / RS, through content analysis and research of the following instruments: the semi-structured interviews with managers and municipal educational mixed school and questionnaires with teachers. We confirm our hypothesis that asserts the existence of such contradictions: between national educational policies of large-scale evaluation of the quality of school education and basic education policies municipal evaluation of educational quality of their school systems, in the final grades of elementary school; between the theory of educational policies of large-scale assessments of educational quality school with educational practices evaluative municipal and school managers and teachers in public schools from elementary schools studied; between educational evaluation of schools practiced based on the pursuit of quality all factors in the teaching-learning process of students and large-scale evaluation of the Brazilian basic education that has the primacy of the quantity of the products or outcomes currently represented by IDEB school. These contradictions are evident under the positivist theoretical perspective, still prevalent in current large-scale evaluation of educational quality Brazilian, which supports to convert the measurement data into quantitative analytical elements relevant in view of the Brazilian school systems, national, state and municipal.
Keywords: Políticas educacionais; Avaliação em larga escala; Qualidade da educação; Cachoeirinha/RS; Educational policies; Evaluation in large-scale; Quality of education; ACCNPQ::Ciências Humanas::Educação